A prospective, randomized parallel-design study to compare two conjunctival approaches in horizontal strabismus surgery: Forniceal versus single-snip paralimbal - Umme Summaiyya; Abadan Khan Amitava; Ziya Siddiqui; Nikita Sharma; Syed Aisha Raza; Ganga Sagar Meena; Karuna Shree; Samuel G Momin (Indian Journal of Ophthalmology)
Purpose: To compare the postoperative course and comfort in strabismus surgeries using the forniceal approach (FA) versus the single-snip paralimbal approach (SSPA). Design: Prospective, randomized, interventional, parallel design study. Methods: We enrolled 60 eyes from 30 consenting patients requiring symmetrical bilateral surgeries, randomizing one eye to the FA or SSPA group. We compared postoperative inflammatory scores individually (redness, congestion, chemosis, foreign body sensation (FBS), and drop intolerance; scored from nil to mild, moderate, or severe on a scale of 0 to 3) and their sum as total inflammatory scores (TIS) on day 1, week 2, and weeks 4–6. We also compared the surgery duration and length of the conjunctival incision. Success was evaluated at weeks 4–6, defined as alignment within 10 PD of orthophoria, and scar visibility was compared. Statistical Analysis: We compared scores using the Wilcoxon test; duration and length with the paired Student’s t-test, and proportions with Fisher’s exact test. Results: Compared to the SSPA, we found significantly lesser FBS, and greater comfort with the FA, evident only until the fortnight following surgery, with no differences thereafter. There were no significant group differences in TIS or the proportions of visible scars: FA vs. SSPA: 4 vs. 7. There were no differences in the length of the incision of number of sutures used to close the incisions. FA took significantly longer (3.6 min). The surgical success rate was 56.7%. Conclusion: Compared to the paralimbal approach, the FA for horizontal rectus muscle surgeries appears to be a better option, providing greater comfort and less FBS in the fortnight following surgery, with a time difference of less than 4 min.